2020
DOI: 10.21203/rs.3.rs-30482/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic Comparison of Changes in Air Quality over China before and during the COVID-19 Pandemic

Abstract: The rapid spread of Covid-19 has affected the political, social, and economic sectors, which inevitably will also affect the environmental component. This contagious virus led the worldwide countries to make securities measures such as lockdown to reduce the spread of COVID-19 and protect human health. In contrast to the negative impacts of this virus on the economy, it has influenced the environment positively. As reported by station and program for monitoring the Earth, the air quality has improved after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…This is primarily because carbon dioxide gas emissions into the atmosphere are reduced based on less industrial activities. This issue is noticeable but not enough for environmental sustainability [2][3][4][5][6]. The Covid-19 pandemic not only affects the air quality index but also affects social mobility during the lockdown because the lockdown demotivates social gatherings.…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily because carbon dioxide gas emissions into the atmosphere are reduced based on less industrial activities. This issue is noticeable but not enough for environmental sustainability [2][3][4][5][6]. The Covid-19 pandemic not only affects the air quality index but also affects social mobility during the lockdown because the lockdown demotivates social gatherings.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the results of a study in Spain, which demonstrated that air pollutants reduced due to lockdown of the COVID-19 outbreak 36 . Another study in China, observed a decrease in emission of NO 2 and an increase in emission of O 3 during the lockdown, especially when the restrictions were removed, more emission of O 3 was experienced 37 . However, the results did not show a significant different between concentration of O 3 during the COVID-19 outbreak (the whole study period) and previous year.…”
Section: Discussionmentioning
confidence: 96%
“…In summer and winter, the lowest concentrations of NO2 (4.3 ppb) and ozone (4.26 µgm/3) were recorded at Teri gram station. This may be due to that in winters, the air pollutants emitted from numerous sources are confined in the boundary layer due to persistent temperature inversions and other conditions such as fewer wind speeds, lower temperatures (Suresh et al, 2020) and lack of rainfall decreased surface vertical mixing which results in less dispersion of air pollutants (Bodor et al, 2020). In general, air molecules are less lively and enforce consolidation and stability in the weather throughout the winter because of the low temperatures, which leads to less dispersion of air contaminants.…”
Section: Seasonal and Monthly Variation Of Air Pollutantsmentioning
confidence: 99%